Intracystic concentrations of tumour markers for the diagnosis of cystic liver lesions. Issue 4 (29th January 2014) - Fuks, D; Voitot, H; Paradis, V; Belghiti, J; Vilgrain, V; Farges, O
Abstract: Background: Imaging occasionally fails to differentiate hepatic simple cysts from malignant or premalignant mucinous cystic lesions such as biliary cystadenomas. Hepatic simple cysts can be treated conservatively, whereas malignant or premalignant cysts require complete resection. This study assessed the ability of intracystic tumour marker concentrations to differentiate these disease entities. Methods: Intracystic fluid was sampled in patients undergoing partial or complete resection of a cystic lesion of the liver. The indication for surgery in hepatic simple cysts was symptoms or suspicion of a biliary cystadenoma. Intracystic concentrations of carcinoembryonic antigen (CEA), carbohydrate antigen (CA) 19-9 and tumour-associated glycoprotein (TAG) 72 were measured to assess the diagnostic accuracy of these tumour markers. Cut-off values were defined by receiver operating characteristic (ROC) curves. Results: The study population comprised 118 patients (94 women) with a median age of 59 years. There were 75 patients with hepatic simple cysts, 27 with mucinous cysts (19 biliary cystadenomas, 4 biliary cystadenocarcinomas, 4 intraductal papillary mucinous neoplasms of the bile duct) and 16 with miscellaneous cysts. Unlike CEA and CA19-9, a TAG-72 concentration of more than 25 units/ml differentiated hepatic simple cysts from mucinous cysts with a sensitivity and a specificity of 0·79 and 0·97 respectively. The area under the ROC curve was 0·98 for mucinous versus hepatic simple cysts. Conclusion: The concentration of TAG-72 in cyst fluid accurately identified hepatic cysts that required complete resection. Abstract : Useful method